2019
DOI: 10.3390/cells8091055
|View full text |Cite
|
Sign up to set email alerts
|

The Redox Role of G6PD in Cell Growth, Cell Death, and Cancer

Abstract: The generation of reducing equivalent NADPH via glucose-6-phosphate dehydrogenase (G6PD) is critical for the maintenance of redox homeostasis and reductive biosynthesis in cells. NADPH also plays key roles in cellular processes mediated by redox signaling. Insufficient G6PD activity predisposes cells to growth retardation and demise. Severely lacking G6PD impairs embryonic development and delays organismal growth. Altered G6PD activity is associated with pathophysiology, such as autophagy, insulin resistance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
146
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(151 citation statements)
references
References 249 publications
(367 reference statements)
5
146
0
Order By: Relevance
“…This pathway generates nucleotides biosynthesis precursors and NADPH for anabolic reactions and redox balance maintenance, which are necessary for cancer cell proliferation. This reaction is only possible in presence of glucose-6-phosphate dehydrogenase (G6PD) (12). G6PD, which is the principal rate-limiting enzyme of the PPP, is the main actor in PPP-mediated cancer progression (8,12).…”
Section: G6pd Facilitates Clear Cell Renal Cell Carcinoma Invasion Bymentioning
confidence: 99%
See 2 more Smart Citations
“…This pathway generates nucleotides biosynthesis precursors and NADPH for anabolic reactions and redox balance maintenance, which are necessary for cancer cell proliferation. This reaction is only possible in presence of glucose-6-phosphate dehydrogenase (G6PD) (12). G6PD, which is the principal rate-limiting enzyme of the PPP, is the main actor in PPP-mediated cancer progression (8,12).…”
Section: G6pd Facilitates Clear Cell Renal Cell Carcinoma Invasion Bymentioning
confidence: 99%
“…This reaction is only possible in presence of glucose-6-phosphate dehydrogenase (G6PD) (12). G6PD, which is the principal rate-limiting enzyme of the PPP, is the main actor in PPP-mediated cancer progression (8,12). Furthermore, G6PD can cooperate with numerous signaling pathways in order to promote cancer, and G6PD was reported to be overexpressed in various types of tumor, including breast carcinoma, ccRCC and lung adenocarcinoma (13)(14)(15).…”
Section: G6pd Facilitates Clear Cell Renal Cell Carcinoma Invasion Bymentioning
confidence: 99%
See 1 more Smart Citation
“…The author in that study proved the reduction in the activity of G6PDH in all samples treated with ACR (table 3), this is may be consider an anther mechanism for ACR action in which ACR directly inhibited G6PDH leading to a reduction of the level of reducing substance NADPH+H consequently reduced the level of GSH as mentioned before, that consider a good explanation on the depletion of GSH and increase of H2O2, MDA and NO, this result in the same line with (Birsen, 2017). G6PDH is the main source of cytoblasmic NADPH+H that necessary of GSH cycle especially in RBCs, the inhibition of G6PDH leads to reduction of NADPH+H and inhibition of GSH cycle leading to increase of free radicals and hemolysis (Hung-Chi et al, 2019). GR and GPx are important enzymes for maintaining the level of GSH, where GPx reduce the free radicals especially H2O2 in presence of GSH producing H2O and GSSG which reduced with GR to GSH.…”
Section: Discussionmentioning
confidence: 99%
“…The work showed that ectopically expressed BAG3 could reduce the growth of HCC cell lines in vitro. Mechanistically, it was found that BAG3 suppressed de novo DNA synthesis by inhibiting the pentose phosphate pathway via direct interaction with the rate-limiting enzyme glucose 6 phosphate dehydrogenase (G6PD) [55]. This growth-deficit could further be rescued either by ectopic expression of G6PD or by nucleosides into the culture medium.…”
Section: Liver Cancermentioning
confidence: 99%